PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII.3 SMP NEGERI 1 TANAH PUTIH KABUPATEN ROKAN HILIR - Aryta, Tamar; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Learning outcomes is the ability gained after the child through learning activities. Each requires a process of learning outcomes developed by teachers with an approach that maximizes student learning outcomes themselves. Contextual approach to teaching and learning is a view in seeking ways students interact with the environment. So whether the approach Contextual Teaching and Learning is relevant research and to improve learning outcomes is the goal of this research. The location in this research that SMP Negeri 1 Tanah Putih Rokan Hilir. Data obtained from the results of observations, the results of student evaluation, and documentation during the study. The number of samples in this study were 23 students consisted of 9 male students and 14 female students. The analysis is the activity of students and teachers, the evaluation result and the thoroughness of the students later described. From the results of research can be concluded that the application of CTL approach can improve learning outcomes IPS VIII.3 grade students of SMP Negeri 1 Tanah Putih Rokan Hilir. From the results of research conducted suggested that teachers should choose an approach CTL as one of the alternative learning approaches in class. For school principals should support the CTL approach adopted by teachers, because if the approach applied learning hasi teachers can improve learning, the quality of teaching success in school will increaseKeywords: Approach Contextual Teaching and Learnign (CTL), Learning Outcomes